2013
DOI: 10.1002/for.2260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Regime Switching Models for Real‐Time Business Cycle Analysis of the Euro Area

Abstract: International audienceIn this paper, we aim at assessing Markov switching and threshold models in their ability to identify turning points of economic cycles. By using vintage data updated on a monthly basis, we compare their ability to date ex post the occurrence of turning points, evaluate the stability over time of the signal emitted by the models and assess their ability to detect in real-time recession signals. We show that the competitive use of these models provides a more robust analysis and detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…We refer for example to the threshold autoregressive (TAR) model, introduced by Tong (1990) or the smooth transition autoregressive (STAR) model, put forward by Teräsvirta (1994), Such models differ from MS models in the sense that the variable governing changes in regimes is observed, leading thus to easier statistical inference. Those models have also proved useful to identify business cycles as shown for example by Deschamps (2008) or Billio et al (2013). However, in this latter paper on euro area data, it has been shown that MS models tend to be more reliable as they send fewer false signals of recessions.…”
Section: Introductionmentioning
confidence: 85%
“…We refer for example to the threshold autoregressive (TAR) model, introduced by Tong (1990) or the smooth transition autoregressive (STAR) model, put forward by Teräsvirta (1994), Such models differ from MS models in the sense that the variable governing changes in regimes is observed, leading thus to easier statistical inference. Those models have also proved useful to identify business cycles as shown for example by Deschamps (2008) or Billio et al (2013). However, in this latter paper on euro area data, it has been shown that MS models tend to be more reliable as they send fewer false signals of recessions.…”
Section: Introductionmentioning
confidence: 85%
“…Our paper also extends Kaufmann (2010), where a panel of univariate Markov-switching (MS) regression models is considered, by constructing a multivariate panel MSVAR structure for the country-specific time series. We build on basic model structures of Hamilton (1989) and Krolzig (2000) and consider Markov-switching dynamics for low and high frequency components that are specified as conditional means and covariance matrices of country-specific equations (see also Billio et al (2012), Basturk et al (2014) and Billio et al (2013b)). We further build on Kaufmann (2015) and use an endogenous time-varying transition mechanism to model the transition matrix of the country-specific Markov-chains.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper also extends Kaufmann (2010), where a panel of univariate Markov-switching (MS) regression models is considered, by constructing a multivariate panel MSVAR structure for the country-specific time series. We build on models of Hamilton (1989) and Krolzig (2000) and consider Markov-switching dynamics for low and high frequency components, that is means and covariance matrices of the country-specific equations (see also Billio et al (2012), Basturk et al (2013) and Billio et al (2013b)).…”
Section: Introductionmentioning
confidence: 99%